The effect of pre-exercise carbohydrate feedings on the intensity that elicits maximal fat oxidation - Achten, J.; Jeukendrup, A. E. (Journal of Sports Sciences, 2003)
The aim of the present study was to examine the effect of ingesting 75 g of glucose 45 min before the start of a graded exercise test to exhaustion on the determination of the intensity that elicits maximal fat oxidation (Fatmax). Eleven moderately trained individuals (VO2max: 58.9 +/- 1.0 ml x kg(-1) x min(-1); mean +/- sx), who had fasted overnight, performed two graded exercise tests to exhaustion, one 45 min after ingesting a placebo drink and one 45 min after ingesting 75 g of carbohydrate in the form of glucose. The tests started at 95 W and the workload was increased by 35 W every 3 min. Gas exchange measures and heart rate were recorded throughout exercise. Fat oxidation rates were calculated using stoichiometric equations. Blood samples were collected at rest and at the end of each stage of the test. Maximal fat oxidation rates decreased from 0.46 +/- 0.06 to 0.33 +/- 0.06 g min(-1) when carbohydrate was ingested before the start of exercise (P < 0.01). There was also a decrease in the intensity which elicited maximal fat oxidation (60.1 +/- 1.9% vs 52.0+3.4% VO2max) after carbohydrate ingestion (P < 0.05). Maximal power output was higher in the carbohydrate than in the placebo trial (346 +/- 12 vs 332 +/- 12 W) (P < 0.05). In conclusion, the ingestion of 75 g of carbohydrate 45 min before the onset of exercise decreased Fatmax by 14%, while the maximal rate of fat oxidation decreased by 28%.